Can restoring wolves aid in lynx recovery? - William J. Ripple; Aaron J. Wirsing; Robert L. Beschta; Steven W. Buskirk (Wildlife Society Bulletin)
Abstract Herein, we examine the hypothesis that relatively low densities of snowshoe hares (Lepus americanus) and the imperiled status of lynx (Lynx canadensis) may be partially due to an ecological cascade caused by the extirpation of gray wolves (Canis lupus) in most of the conterminous United States decades ago. This hypothesis focuses on 2 plausible mechanisms, one involving “mesopredator release” of the coyote (C. latrans), which expanded its distribution and abundance continentally following the ecological extinction of wolves over the temperate portion of their geographic range. In the absence of wolves, coyotes may have affected lynx via increased predation on snowshoe hares, on which the lynx specializes, and/or by direct killing of lynx. The second mechanism involves increased browsing pressure by native and domestic ungulates following the declines in wolves. A recovery of long‐absent wolf populations could potentially set off a chain of events triggering a long‐term decrease in coyotes and ungulates, improved plant communities, and eventually an increase in hares and lynx. This prediction, and others that we make, are testable. Ecological implications for the lynx may be dependent upon whether wolves are allowed to achieve ecologically effective populations where they recolonize or are reintroduced in lynx habitat. We emphasize the importance of little‐considered trophic and competitive interactions when attempting to recover an endangered carnivore such as the lynx. © 2011 The Wildlife Society.